Penerapan Pendekatan Proses Belajar Sole (self organized learning environment) pada Sistem Ekskresi untuk Meningkatkan Keterlibatan dan Capaian Akademik Siswa - Hendra Wijaya; Supardi U. S (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The Biology learning process at SMAN 3 Cibeber still produces achievements that are not optimal, this condition is due to the application of a more dominant conventional learning process approach, where teachers often use lectures rather than actively involve students. This study adopts a quantitative approach with an experimental design to test the effect of the application of the sole learning process approach on students' academic activities and achievements. The subject of this study is grade XI students in the 2024/2025 Academic Year. A total of 25 students were selected for the experimental class and another 25 students for the control class. This study uses a quasi-experimental design with data collection through initial evaluation and final evaluation. The data obtained was analyzed using the paired sample T-test. The results of the analysis showed a significance value of 0.000, which is smaller than 0.05, indicating a significant difference in the academic achievement of students in experimental classes that applied the sole learning process. The increase in students' cognitive academic achievement can be seen from the N-Gain value of 0.46 which is included in the medium category. These findings show that the application of the sole learning process in the excretory system learning process can increase both student engagement and academic achievement.